Penerapan Sistem Informasi Berbasis Web untuk Optimalisasi Pengelolaan Jadwal Kegiatan dan Penyampaian Informasi kepada Jamaah Masjid An-Nur Tambah Dadi - Roro Fatikhin; Nuari Anisa Sivi; Imam Mualim; Khoirul Anam (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The development of information technology has driven digital transformation in various sectors, including the management of religious organizations. Mosques, as centers of worship, education, and community empowerment, require an information management system capable of supporting the delivery of information quickly, accurately, and easily accessible to the congregation. An-Nur Mosque, located in Tambah Dadi Village, Purbolinggo District, East Lampung Regency, was completed in June 2025 and began holding various religious activities regularly. However, information management is still carried out conventionally through verbal announcements and information boards, so the reach of information delivery is not optimal. This community service activity aims to implement a web-based information system as a medium for managing activity schedules and delivering information to the congregation while simultaneously increasing the capacity of administrators in managing information services digitally. The implementation method uses a Participatory Action Research (PAR) approach that includes the stages of needs analysis, system design, website implementation, training and mentoring for administrators, and program evaluation. The website was developed with various features, including a mosque profile, management structure, activity schedule, news and announcements, activity documentation, a photo gallery, and information on mosque construction. The results of the activity indicate that the web-based information system was successfully implemented and utilized as the official information medium for the An-Nur Mosque. The training and mentoring provided improved the administrators' ability to manage the website independently. The evaluation also showed that the website facilitated information delivery, supported the management of activity documentation, increased administrative effectiveness, and expanded congregational access to mosque information. Thus, the implementation of the web-based information system has been proven to positively contribute to improving the quality of information governance at the An-Nur Mosque and has the potential to become a model for digitalizing information management for other mosques with similar characteristics.